Aplikasi Penyewaan Motor Berbasis Lokasi Dengan Navigasi Dan Pemesanan Real Time - Faizin, Ahmad; Kalifia, Anna Dina (STMIK Banjarbaru, 2024)
Transmojo encountered challenges in delivering efficient motorcycle rental services due to the lack of a digital application that supports booking and navigation processes. This research focuses on developing an Android-based application integrated with the Google Maps API and a Real-time database to provide instant information on motorcycle availability. The application was developed using Kotlin for the Android platform, with Firebase serving as the database. The development process followed the V-Model approach, applying verification and validation at every stage to ensure the proper functioning of all features. Testing was carried out using the black-box method. The results indicate that the application performs well, enhancing the efficiency of the booking process and offering a smoother navigation experience for users. This application is expected to simplify the rental process, improve customer satisfaction, and support the growth of motorcycle rental services at Transmojo.Keywords: Motorcycle rental; Android; Google Maps API; Real-time; V-ModelÂ AbstrakTransmojo mengalami kendala dalam memberikan layanan penyewaan motor yang efisien karena tidak adanya aplikasi digital yang mendukung proses pemesanan dan navigasi. Penelitian ini berfokus pada pengembangan aplikasi berbasis Android yang terintegrasi dengan Google Maps API dan database Real-time untuk menampilkan informasi ketersediaan motor secara langsung. Aplikasi ini dibangun menggunakan Kotlin untuk platform Android dan Firebase sebagai basis data. Metodologi pengembangan mengikuti pendekatan V-Model, dengan penerapan verifikasi dan validasi di setiap tahap guna memastikan semua fungsi berjalan dengan optimal. Pengujian dilakukan menggunakan metode Black-Box Testing. Hasil menunjukkan bahwa aplikasi berfungsi dengan baik, meningkatkan efisiensi pemesanan, dan memberikan pengalaman navigasi yang lebih nyaman bagi pengguna. Aplikasi ini diharapkan dapat mempermudah proses penyewaan, meningkatkan kepuasan pelanggan, dan mendukung pertumbuhan layanan penyewaan motor di Transmojo.Â